1963
DOI: 10.4141/cjps63-023
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Planting Pattern on Yield, Per Cent Oil and Per Cent Protein in Mandarin (Ottawa) Soybeans

Abstract: The performance of Mandarin (Ottawa) soybeans was tested over a 4-year period in fifteen planting patterns resulting from five row spacings \i,74,21,28 and 35 inches) and-three plant spacings (1,2, and 3.inches) within the row. Response of yield and oil percentage to spacing was considerable. The combination of narrowest row and widest pllnt spacing within the row (7 X 3) gave the high.est yield, whereas highest per cent oil was obtained from the widest row and the widest plant spacins (35 X 3)' One year of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
12
0

Year Published

1966
1966
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 1 publication
4
12
0
Order By: Relevance
“…Debranching at low densities was also associated with premature senescence of leaves and desiccation of immature pods, suggesting that branch removal need not have an exclusively simple nutritional basis. High canopy density reduced oil content, and seeds borne on primary racemes had lower oil levels than those on axillary branches.Reports on several crops indicate that spacing affects the percentage of oil in harvested seed (Dillman and Brinsmade, 1938;Hinson and Hanson, 1962;Donovan et al, 1963). In preliminary experiments forming part of the present study it was also observed that seed borne on secondary racemes could develop a higher oil content than those on the primaries, though the increased oil levels were generally found only when plants were grown in dense stands.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Debranching at low densities was also associated with premature senescence of leaves and desiccation of immature pods, suggesting that branch removal need not have an exclusively simple nutritional basis. High canopy density reduced oil content, and seeds borne on primary racemes had lower oil levels than those on axillary branches.Reports on several crops indicate that spacing affects the percentage of oil in harvested seed (Dillman and Brinsmade, 1938;Hinson and Hanson, 1962;Donovan et al, 1963). In preliminary experiments forming part of the present study it was also observed that seed borne on secondary racemes could develop a higher oil content than those on the primaries, though the increased oil levels were generally found only when plants were grown in dense stands.…”
supporting
confidence: 58%
“…Reports on several crops indicate that spacing affects the percentage of oil in harvested seed (Dillman and Brinsmade, 1938;Hinson and Hanson, 1962;Donovan et al, 1963). In preliminary experiments forming part of the present study it was also observed that seed borne on secondary racemes could develop a higher oil content than those on the primaries, though the increased oil levels were generally found only when plants were grown in dense stands.…”
supporting
confidence: 58%
“…Crude protein and oil concentrations, which are negatively correlated, were previously reported to be affected by a range of environmental conditions and agronomic practices, including row spacing, weed control, and planting dates; reports have, however, been conflicting and differences were often minor (Donovan et al 1963;Rose 1988;Kane et al 1997;Galal 2004). …”
Section: Crude Protein and Oil Concentrationsmentioning
confidence: 99%
“…Donovan et al (1963) Cooper (1977) and Wax et al (1977), who demonstrated higher yields in narrow rows (( 25 cm) than in wide rows (> 50 cm) in central Illinois. Wiggans (1939) According to Willey and Heath (1969) plant population should not be defined in terms of density alone, but also in terms of rectangularity or the spatial arrangement of 228 CANADIAN JOURNAL OF PLANT SCIENCE the plants.…”
mentioning
confidence: 94%